Are plasma mineral levels related to antibody response to influenza vaccination in older adults?. Issue 4 (2nd April 2016) - Kaynar, Ata Murat; Nowalk, Mary Patricia; Lin, Chyongchiou Jeng; Moehling, Krissy K.; Susick, Michael; Bakalov, Veli; Pitt, Bruce R.; Bain, Daniel J.; Ross, Ted M.; Saul, Sean G.; Raymund, Mahlon; Zimmerman, Richard K.
Abstract: Introduction : An effective immune response to vaccination may be related to nutritional status. This study examined the association of plasma mineral levels with hemagglutination inhibition (HI) titers produced in response to influenza vaccine in older adults.Methods : Prior to (Day 0) and 21 (range = 19–28) days after receiving the 2013–14 influenza vaccine, 109 adults ages 51–81 years, provided blood samples. Serum samples were tested for HI activity against the A/H1N1 and A/H3N2 2013–2014 vaccine virus strains. Plasma minerals were collected in zinc-free tubes and assayed by inductively coupled plasma mass spectrometry. HI titers were reported as seroprotection (≥1:40) and seroconversion (≥ 4-fold rise from Day 0 (minimum HI = 1:10) to Day 21). Both HI titers and mineral values were skewed and thus log2 transformed. Magnesium (Mg), phosphorus (P), zinc (Zn), copper (Cu), iron (Fe), potassium (K) and the Cu to Zn ratio were tested. Logistic regression analyses were used to determine the associations between mineral levels and seroconversion and seroprotection of HI titers for each influenza A strain.Results : Participants were 61% white, 28% male, 39% diabetic, and 81% overweight/obese with a mean age of 62.6 y. In logistic regression, Day 21 A/H1N1 seroprotection was associated with P and Zn at Day 21( P < 0.05). Seroconversion of A/H1N1 was associated with Day 21 Cu, P, and Mg ( P < 0.03). Day 21 A/H3N2 seroprotection and seroconversion were associated with Day 21 P ( P < 0.05).Conclusions : Phosphorus was associated with seroprotection and seroconversion to influenza A after vaccination; these associations warrant additional studies with larger, more diverse population groups.